2020
DOI: 10.3329/baj.v23i1.50122
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Garlic (Allium Sativum) With Chilli (Capsicum Annuum L.) in the Haor Area of Kishoreganj

Abstract: Haor is one of the uncertain areas for crop production and productivity in Bangladesh. Traditionally, single cropping practice in a short cropping season is the key obstacle to increase crop productivity. A study was carried out at Multi Location Testing site (MLT), Nikly under the On-Farm Research Division (OFRD), Bangladesh Agricultural Research Institute (BARI), Kishoreganj at haor area during the two consecutive Rabi seasons of 2015-16 and 2016-17 to evaluate the performance of garlic with chilli intercrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Intercrops significantly reduced the yield of main crop as compared to sole cropping. Similar results were recorded by Khatun et al, [4].…”
Section: Growth Yield and Quality Characters Of Chillisupporting
confidence: 92%
See 1 more Smart Citation
“…Intercrops significantly reduced the yield of main crop as compared to sole cropping. Similar results were recorded by Khatun et al, [4].…”
Section: Growth Yield and Quality Characters Of Chillisupporting
confidence: 92%
“…Kadir et al, [11] observed that chilli and groundnut intercropping systems increased yield, economic and nutritional value. Besides this, many researchers also indicated that intercropping practice gets a higher economic return than the sole cropping practice (Razzaque et al, 2007; Suresha et al, [12]; Alom et al, [13]; Bhuiyan et al, [14]; Farhad et al, [15]; Begum et al, [3], Khatun et al, [4]).…”
Section: Cost Benefit Analysismentioning
confidence: 99%
“…Kadir et al [8] observed that chilli and groundnut intercropping systems increased yield, economic and nutritional value. Besides that, many researchers also indicated that intercropping practice gets a higher economic return than the sole cropping practice [9,10,1,11,12]. T1 Sole Chilli @100% RDF, T4 Chilli @ 80% RDF + Carrot @20% RDF, T5 Chilli @ 80% RDF+ Radish @20% RDF, T6 Chilli @70% RDF + Carrot @30% RDF, T7 Chilli @ 70% RDF + Radish @ 30% RDF, T8 Chilli @ 60%RDF+Carrot@20%RDF+Radish @20%RDF T2 Sole Carrot @100% RDF, T4 Chilli @ 80% RDF + Carrot @20% RDF, T6 Chilli @70% RDF + Carrot @30% RDF, T8 Chilli @ 60%RDF+Carrot@20%RDF+Radish @20%RDF T3 Sole Radish @100% RDF, T5 Chilli @ 80% RDF+ Radish @20% RDF, T7 Chilli @ 70% RDF + Radish @ 30% RDF, T8 Chilli @ 60%RDF+Carrot@20%RDF+Radish @20%RDF.…”
Section: Cost Benefit Analysismentioning
confidence: 99%
“…Kadir et al [3] observed that chilli and groundnut intercropping systems increased yield, economic and nutritional value. Besides this, many researchers also indicated that intercropping practice gets a higher economic return than the sole cropping practice [4][5][6][7][8][9][10][11][12]. T1 Sole Chilli @100% RDF, T4 Chilli @ 85% RDF + Coriander @15% RDF, T5 Chilli @ 85% RDF+ Fenugreek @15% RDF, T6 Chilli @70% RDF + Coriander @30% RDF, T7 Chilli @ 70% RDF + Fenugreek @ 30% RDF, T8 Chilli @ 60%RDF+Coriander@20%RDF+Fenugreeek @20%RDF T2 Sole Coriander @100% RDF, T4 Chilli @ 85% RDF + Corinader @ 15 % RDF, T6 Chilli @70% RDF + Coriander @30% RDF, T8 Chilli @ 55 % RDF + Coriander @ 22.5 % RDF + Fenugreek @ 22.5 % RDF T3 Sole Fenugreek @100% RDF, T5 Chilli @ 85% RDF+ Fenugreek @15% RDF, T7 Chilli @ 70% RDF + Fenugreek @ 30% RDF, T8 Chilli @ 55%RDF+Coriander @ 22.5 % RDF + Fenugreek @ 22.5 % RDF T1 Sole Chilli @100% RDF, T2 Sole Coriander @100% RDF, T3 Sole Fenugreek @100% RDF, T4 Chilli @ 85% RDF + Coriander @15% RDF, T5 Chilli @ 85% RDF+ Fenugreek @15% RDF, T6 Chilli @70% RDF + Coriander @30% RDF, T7 Chilli @ 70% RDF + Fenugreek @ 30% RDF, T8 Chilli @ 55 % RDF + Coriander @ 22.5 % RDF+ Fenugreek @ 22.5 % RDF…”
Section: Cost Benefit Analysismentioning
confidence: 99%